Perilaku Pengelolaan Keuangan Dan Pengambilan Keputusan Finansial Oleh Driver Ojek Online Maxim Di Kota Surakarta - Sanusi Dwiky Sanyoto; Aris Eddy Sarwono (Pusat Riset dan Inovasi Nasional, 2025)
This study aimed to examine the financial management practices and decision-making of Maxim drivers in Surakarta. The qualitative approach was used by interviewing twenty drivers as informants through in-depth interviews. Thematic data analysis was employed to find recurring patterns of financial management practice in the context of being online motorcycle taxi drivers. The findings reveal that the majority of drivers dispense their wages based on immediate needs, preferring immediate consumption such as fuel and food. Monetary decision-making is primarily driven by income uncertainty, with the majority of drivers accepting all incoming trips despite the fairly low fare. Moreover, the research shows that there is a distinct financial management pattern among online motorcycle taxi drivers who are also students, allocating a portion of their income regularly for tuition payments. Based on these findings, the research concludes that there is a necessity for improved financial literacy education among online motorcycle taxi drivers and that these must be supported by technologies to help them manage their finances better.